Numerical and experimental transition results evaluation for a morphing wing and aileron system. (12th April 2018) - Botez, R.M.; Koreanschi, A.; Gabor, O.S.; Tondji, Y.; Guezguez, M.; Kammegne, J.T.; Grigorie, L.T.; Sandu, D.; Mebarki, Y.; Mamou, M.; Amoroso, F.; Pecora, R.; et al.
ABSTRACT: A new wing-tip concept with morphing upper surface and interchangeable conventional and morphing ailerons was designed, manufactured, bench and wind-tunnel tested. The development of this wing-tip model was performed in the frame of an international CRIAQ project, and the purpose was to demonstrate the wing upper surface and aileron morphing capabilities in improving the wing-tip aerodynamic performances. During numerical optimisation with 'in-house' genetic algorithm software, and during wind-tunnel experimental tests, it was demonstrated that the air-flow laminarity over the wing skin was promoted, and the laminar flow was extended with up to 9% of the chord. Drag coefficient reduction of up to 9% was obtained when the morphing aileron was introduced.